Peningkatan Hasil Belajar IPA dengan Menerapkan Metode Example Non Example - Husna, Putri Nurizatul; Supandi, Hermaya (Journal of Development Education and Learning (JODEL), 2023)
It is found a few symptoms or phenomena in the process of teaching and learning that demonstrates the low level of student learning outcomes, including: the results obtained studying students not optimal, it is visible on the results of the evaluation on subjects’ natural science, student learning outcomes is still low at the lower value of the KKM has set that is 65. Students impressed difficult to understand material presented by the teacher in the class IV A SD Negeri Padang Broad Sub 005 Mine District of Kampar. This research was conducted in two cycles each cycle consists of two times. The stages in the research, planning, execution is action, observation, reflection. Research results on the initial data indicate that the results of the study before the action is performed with achievement 40%, after corrective action turns the results of student learning increased in cycles I 60%, then in cycle II also improved 96,66% meaning in classical or overall learning outcomes are on the increase. With this in mind an increase in student learning results on subjects Natural Science by applying the method of Example non-Example in class IV The State elementary school 005 Padang   Luas of Tambang Sub District of Kampar regency.